Power Quality Analysis of a 20kV Primary Distribution Line Using ETAP Power Station 12.6.0 at Sidikalang Substation - Arnawan Hasibuan; Rizki Yaldi; Muchlis Abdul Muthalib; Muhammad; Dedi Fariadi (Proceedings of International Conference on Multidisciplinary Engineering (ICOMDEN), 2024)
The rapid economic growth and population increase in Indonesia have significantly raised the demand for electrical energy. The electricity distribution system, having the highest rate of disruptions among power system components, has become the primary focus for improvement efforts. This study aims to evaluate the quality of electricity distribution lines at the Sidikalang Substation using ETAP Power Station 12.6.0. The analysis is crucial for understanding power usage efficiency, identifying potential disturbances, and evaluating distribution system performance. The main challenge lies in effectively evaluating distribution line quality, involving the monitoring of critical parameters such as voltage, current, and power factor. Utilizing ETAP Power Station 12.6.0 enables in-depth analysis, aids decision-making, and facilitates future planning. This research draws upon scientific literature and industry guidelines to provide a strong theoretical foundation. The study's findings are expected to contribute to enhancing the quality and reliability of electricity distribution systems in Indonesia, thereby supporting the nation's sustainable development goals in the energy sector.